Aberrant Hematopoiesis and Morbidity in Extremely Preterm Infants With Intrauterine Growth Restriction - Reibel, Nora J.; Dame, Christof; Bührer, Christoph; Muehlbacher, Tobias (Frontiers in Pediatrics, 2021)
Background and objective: Intrauterine growth restriction (IUGR) poses additional challenges in extremely low gestational age newborns (ELGANs). We assessed disturbed hematopoiesis and morbidities associated with this disorder. Methods: This single-center retrospective case-control study compared perinatal hematological profiles, major morbidities and mortality of 49 infants (gestational age <28 weeks, birth weight ≤3rd percentile and compromised placental function), and 98 infants (birth weight >10th percentile) matched for gestational age, year and sex. Results: IUGR-ELGANs had significantly elevated nucleated red blood cells, lower neutrophil and platelet counts at birth and on the 3rd day of life. During the first week of life, IUGR-ELGANs received more red blood cell, platelet and plasma transfusions and were more intensively treated with antibiotics. Rates of infections acquired during the first week (59.2% vs 17.3%, p<.001), severe bronchopulmonary dysplasia or death (42.9% vs 17.3%, p<.01) and mortality (36.7% vs 7.1%, p<.001) were markedly elevated in IUGR-ELGANs, but not of hemorrhages or other morbidities. Conclusions: IUGR-ELGANs have high rates of acquired infections during the first week of life and display severe pulmonary morbidity leading to bronchopulmonary dysplasia or death. The high rate of transfusions observed in these infants warrants further scrutiny.